Evaluation of recovering the "Tuvacobalt” Mining and Processing Complex: accounting the ecology factor - Dabiev, David F. (The New Research of Tuva, 2014)
The article describes the various options for recovery of the "Tuvacobalt” Mining and Processing Complex that worked on the mineral resources base of Khovu-Aksy nickel-cobalt deposit between 1970 and 1990’s. It shows that in case of revival combined with innovative technologies the project will have a relatively higher economic efficiency.
Keywords: cobalt production; nickel; economic evaluation; Tuvacobalt; innovation; ecology